2015
DOI: 10.1002/ange.201509302
|View full text |Cite
|
Sign up to set email alerts
|

A Catalyst Designed for the Enantioselective Construction of Methyl‐ and Alkyl‐Substituted Tertiary Stereocenters

Abstract: Tertiary methyl-substituted stereocenters are present in numerous biologically active natural products.R eported herein is acatalytic enantioselective method for accessing these chiral building blocks using the Mukaiyama-Michael reaction between silyl ketene thioacetals and acrolein. To enable remote enantioface control on the nucleophile,anew iminium catalyst, optimizedb yt hree-parameter tuning and by identifying substituent effects on enantioselectivity,w as designed. The catalytic process allows rapid acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These two structural features are known to be correlated with the energy of the system. 8,30 After the first batch of calculations, we found that a conformation label with two features is insufficient and conformers with the same conformation label can have a ΔΔG up to 6 kcal mol −1 . By inspecting the difference in structure between conformers with the same conformation label, we picked out other important structural features and introduced them into the conformation labelling system.…”
Section: Automations and Conformation Analysesmentioning
confidence: 99%
“…These two structural features are known to be correlated with the energy of the system. 8,30 After the first batch of calculations, we found that a conformation label with two features is insufficient and conformers with the same conformation label can have a ΔΔG up to 6 kcal mol −1 . By inspecting the difference in structure between conformers with the same conformation label, we picked out other important structural features and introduced them into the conformation labelling system.…”
Section: Automations and Conformation Analysesmentioning
confidence: 99%
“…[86] In order to obtain high levels of enantioselectivity,t he authors designed an ew pyrrolidinec atalyst 169 which bears an aryl substituent at the C5 position since the use of other amino catalystss uch as MacMillan's( 160), or a C2-symmetric 2,5-diphenylpyrrolidine catalyst, afforded lower values. [86] In order to obtain high levels of enantioselectivity,t he authors designed an ew pyrrolidinec atalyst 169 which bears an aryl substituent at the C5 position since the use of other amino catalystss uch as MacMillan's( 160), or a C2-symmetric 2,5-diphenylpyrrolidine catalyst, afforded lower values.…”
Section: Organocatalytic Mukaiyama-michael Reactions 41 Imidazolidimentioning
confidence: 99%
“…Recently,P ihko et al have also described the reactions of acrolein 167 with silyl ketene thioacetals 168 in the presence of ac hiral pyrrolidine 169 to give a-alkyl substituted thioesters 170 (Scheme 59). [86] In order to obtain high levels of enantioselectivity,t he authors designed an ew pyrrolidinec atalyst 169 which bears an aryl substituent at the C5 position since the use of other amino catalystss uch as MacMillan's( 160), or a C2-symmetric 2,5-diphenylpyrrolidine catalyst, afforded lower values. Catalyst 169,c ontaining electron-donating substituents at the aryl groups,g ave the best results from an enantioselectivity and conversion standpoint.…”
Section: Organocatalytic Mukaiyama-michael Reactions 41 Imidazolidimentioning
confidence: 99%
See 1 more Smart Citation